Investigating the Nature Of Science: An Empirical Report on the Teacher Development Program in Thailand - Prachagool, V.; Nuangchalerm, P. (Jurnal Pendidikan IPA Indonesia, 2019)
Nature of Science (NOS) is a basic of understandings how science concerns human lives and social development. If the nature of science is a loss in science education and its implementation, the concept of science learning is failed in science education philosophy. Preservice teachers are initial key factors to introduce and implement NOS for those students. This study investigates understandings of nature of the science of preservice science teachers from bachelor study in science education program. Participants are 121 preservice science teachers who enrolled in the second semester in the academic year 2017 from a university in the northeast of Thailand. Questionnaires via Google Forms were used for data collection. Descriptive statistics and qualitative data were provided. Data were analyzed and grouped by level of understandings of NOS. A correlation was also studied for testing different understandings. The findings indicated their understandings to meet the goal of science education, understandings need to embed NOS in curriculum and instruction. Some understandings of participants seem to be not understandable. It needs more discussion and explorations for future enhancement of understandings of NOS through the teacher preparation program.